2014
DOI: 10.1051/shsconf/20141201004
|View full text |Cite
|
Sign up to set email alerts
|

Internal Market Orientation Framework as a Source of Improving Service Quality within the Malaysian Hotel Industry

Abstract: Abstract. This paper is developed as a means to discover the importance of improving service quality within the Malaysian Hotel Industry. To support that contention it was found that there are a number of methodologies or approaches that can be used to improve service delivery. Recent publications show that there is an emerging methodology sought to improve employee performance and one of the approaches are known as Internal Market Orientation. The Internal Market Orientation model consists of three dimensions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…In relation to the employee performance, several studies have been done to investigate the role of effective internal communication practices toward employee outcomes such as work attitudes and employee performance (e.g., Billy & To, 2013;Olson-Buchanan & Boswell, 2006). In the same vein Lahap, Said, Rose, Sumarjan, and Mohi (2014) found that effective communication practices contribute to improving service quality. Similar findings concluded by the Gounaris (2008) training and the effective communication system has an influence on the quality of frontline employee's service delivery and the satisfaction of employees.…”
Section: Internal Communicationmentioning
confidence: 99%
“…In relation to the employee performance, several studies have been done to investigate the role of effective internal communication practices toward employee outcomes such as work attitudes and employee performance (e.g., Billy & To, 2013;Olson-Buchanan & Boswell, 2006). In the same vein Lahap, Said, Rose, Sumarjan, and Mohi (2014) found that effective communication practices contribute to improving service quality. Similar findings concluded by the Gounaris (2008) training and the effective communication system has an influence on the quality of frontline employee's service delivery and the satisfaction of employees.…”
Section: Internal Communicationmentioning
confidence: 99%
“…Dhillon (2013) indicated that image is an important element of a hotel; a brand acts as the most influential element in services because of its natural uniqueness like perish ability, inseparability, tangibility and heterogeneity. Lahap et al (2014) stated that hotel image is also an important variable that positively or negatively influences marketing strategies of the hotel itself.…”
Section: Hotel Imagementioning
confidence: 99%